Mycological Profile and Its Associated Factors Among Patients Suspected of Dermatophytosis at Bisidimo Hospital, Eastern Ethiopia - Ali Dawa M; Tesfa T; Weldegebreal F (Dove Medical Press, 2021)
Mina Ali Dawa,1 Tewodros Tesfa,2 Fitsum Weldegebreal2 1Department of Veterinary Medicine, College of Veterinary Medicine, Haramaya University, Haramaya, Ethiopia; 2Department of Medical Laboratory Sciences, College of Health and Medical Science, Haramaya University, Harar, EthiopiaCorrespondence: Fitsum WeldegebrealDepartment of Medical Laboratory Sciences, College of Health and Medical Science, Haramaya University, P.O. Box: 235, Harar, EthiopiaEmail fwmlab2000@gmail.comBackground: Dermatophytosis is a common problem across the globe that is caused by a group of closely related fungi known as the dermatophytes that can invade keratinized tissues. It is a usual refractory infection and deleteriously affects the quality of life of humans. Despite the common presence of dermatophytes on the human host, research evidence in this area is limited.Objective: Aimed to assess the mycological profile and its associated factors among patients suspected of dermatophytosis at Bisidimo Hospital, Eastern Ethiopia, from March to October 2021.Methods: A cross-sectional study was conducted on 289 patients who visited the dermatology department of Bisidimo Hospital. Data were collected by reviewing patients' charts and using a structured questionnaire to assess the associated factors of dermatophytosis. The patients' medical charts were reviewed to assess chronic conditions. Skin, hair, or nail samples were collected and transported to Medical Microbiology Laboratory at Haramaya University Department of Medical Laboratory Sciences. Samples were inoculated into Potato dextrose agar and Sabouraud dextrose agar, and fungal isolates were identified morphologically and microscopically. Data were analyzed using Statistical Package for the Social Sciences version 26. Bivariate and multivariable logistic regression analyses with 95% confidence intervals were carried out to identify factors associated with dermatophytosis.Results: The overall magnitude of dermatophytosis infection was 28.4% (95%CI: 23.2- 32.2). Tinea capitis and tinea corporis were the common clinical presentations. The fungal isolates include Trichophyton species (68 isolates) and Epidermophyton species (17 isolates). Patients with features involving male sex (AOR = 2.5), age group of 1- 10 years (AOR = 3.5), hypertension (AOR = 2.2), a family history of dermatophytosis (AOR = 2.0), and a history of animal contact (AOR = 1.5) had the increased odds of being infected with the dermatophytosis.Conclusion: We found more than one in four patients assessed had dermatophytosis infection. It was considerably high in patients with a family history of the infection, animal contacts, hypertension, and below 10 years of age. Therefore, the control program for this disease should specifically target at a high risk populations, which must hinge on the evidence of molecular characterization and antifungal susceptibility patterns of the fungi.Keywords: dermatophytosis, mycological profile, patients, Bisdimo, Ethiopia